Proposed Layout for Goods Storage in RM Supermarket Warehouse Using Dedicated Storage - Masniar, Masniar; Wahyudien, Mohammad Arief Nur; Ahistasari, Asih; Karyanto, Agus; Tajuddin, Tamrin (PT. SAFARI AMALIA, 2025)
The warehouse is one of the most important components of the business. Activities storage covering receipt, storage, arrangement, bookkeeping, maintenance, and disbursement of goods from the storage place. When the warehouse lacks proper management, goods are not arranged by type or classification. Goods are piled up in one place because the warehouse does not have enough space. Therefore, when taking goods, must dismantle and move the appropriate goods. Thus, the process of taking and storing goods takes quite a long time. Planning layout means building and integrating flow components for the product so that operators, equipment, and material transformation processes interact most efficiently from part reception to part delivery, which is also known as the location storage still with the Dedicated Storage method. Research results indicate two proposed storage layout options. The First Alternative​ produces the total distance of 281.9 meters by subtracting 55.8 meters, or 6.6%, from the current layout. Meanwhile, the alternative second produce distance is 373.9 meters, with a subtraction distance of -36.3 meters, or -10%. Of the two choices, alternative 1 is more efficient than alternative 2.